The effect of preoperative training on functional recovery in patients undergoing total knee arthroplasty: A systematic review and meta-analysis. (March 2018) - Ma, Jian-xiong; Zhang, Lu-kai; Kuang, Ming-jie; Zhao, Jie; Wang, Ying; Lu, Bin; Sun, Lei; Ma, Xin-long
Abstract: Objective: A meta-analysis to evaluate the efficacy of preoperative training on functional recovery in patients undergoing total knee arthroplasty. Method: Randomized controlled trials (RCTs) about relevant studies were searched from PubMed (1996–2017.4), Embase (1980–2017.4), and the Cochrane Library (CENTRAL 2017.4). Nine studies which evaluated the effect of preoperative training on functional recovery in patients undergoing TKA were included in our meta-analysis. Meta-analysis results were collected and analyzed by Review Manager 5.3 (Copenhagen: The Nordic Cochrane Center the Collaboration 2014). Results: Nine studies containing 777 patients meet the inclusion criteria. Our pooled data analysis indicated that preoperative training was as effective as the control group in terms of visual analogue scale(VAS) score at ascend stairs (P = 0.41) and descend stars (P = 0.80), rang of motion (ROM) of flexion (P = 0.86) and extension (P = 0.60), short form 36 (SF-36) of physical function score (P = 0.07) and bodily pain score (P = 0.39), western Ontario and Macmaster universities osteoarthritis index (WOMAC) function score (P = 0.10), and time up and go (P = 0.28). While differences were found in length of stay (P < 0.05). Conclusions: Our meta-analysis demonstrated that preoperative training have the similar efficacy on functional recovery in patients following total knee arthroplasty compared with control group. However, high quality studies with more patients were needed in future. Highlights: We made this meta-analysis to evaluate the efficacy of preoperative training programme on functional recovery in early post-operative periods after TKA. Preoperative training will not improve the ROM in patients received TKA.